Okno McLuhana. McLuhan w teorii i praktyce. Jutro widziane dzisiaj - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
Marshall McLuhan was one of the most significant and influential, not to mention popular, mass media researchers and commentators. The article offers a detailed introduction to the essential methodology of his works. By taking a fresh approach, this study explores and explains the basic structure of McLuhan’s method for describing, analysing and interpreting various themes and phenomena connected with media communication, emphasizing the key relationship between theory and practice as a way leading toward “understanding media”.